INTERBLOCK ZONES IN THE CRUST OF THE SOUTHERN REGIONS OF EAST SIBERIA: TECTONOPHYSICAL INTERPRETATION OF GEOLOGICAL AND GEOPHYSICAL DATA - K. Zh. Seminsky; N. O. Kozhevnikov; A. V. Cheremnykh; E. V. Pospeeva; A. A. Bobrov; V. V. Olenchenko; M. A. Tugarina; V. V. Potapov; R. M. Zaripov; A.S. Cheremnykh (Геодинамика и тектонофизика)
The zone-block structure of the lithosphere is represented by a hierarchically organized pattern of stable blocks and mobile zones which border such blocks and contain highly dislocated geological medium (Fig. 1). Today, different specialists adhere to different concepts of blocks and zones, which are two main elements of the lithosphere structure. Differences are most significant in determinations of ‘interblock zones’ that are named as deformation / destructive / contact / mobile / fracture zones etc. due to their diversity in different conditions of deformation. One of the most effective approaches to studying the zone-block structure of the lithosphere is a combination of geological and geophysical studies of interblock zones tectonic features on various scales, which can make it possible to reveal the most common patterns of the interblock zones, general regularities of their development and relationships between the interblock zones.The main objectives of our study were (1) to identify the zone-block structure of the crust in the southern regions of East Siberia from tectonophysical analysis of geological and geophysical surveys conducted on four different scales along the 500 km long Shertoy-Krasny Chikoy transect crossing the marginal segment of the Siberian block, the Baikal rift and the Transbaikalian block (Fig. 2); (2) to clarify structural features of the central part of the Baikal rift (representing the tectonic type of interblock extension zone) by applying new research methods, such as radon emanation survey, to the Shertoy-Krasny Chikoy transect and using the previously applied methods, such as magnetotelluric sounding, on a smaller scale; and (3) to study manifestation of interblock zones of various ranks in different geological and geophysical fields, to reveal common specific features of their structural patterns for the upper crust, and to establish regularities of hierarchic and spatial relationships between the interblock zones.On the global scale, the object of our study at the Shertoy-Krasny Chikoy transect was the Baikal interblock zone (Fig. 2, 15, and 16). On the trans-regional scale, large fault zones were studied (Fig. 6, 11, and 14). On the regional and local scales, the objects of our study were systems of faults and fractures of various ranks which were active at the late Cenozoic stage of tectogenesis (Fig. 4, and 5). The set of geological and geophysical surveys included application of methods for identification of faults and fractures using different criteria, with account of the fact that clusters of such structures are indicative of the interblock zones of the crust. We used structural geological methods for studying faults and fractures, morphostructural analysis (including interpretation of satellite images), self-potential (SP) and resistivity profiling, magnetotelluric (MT) sounding, radon emanation survey, and hydrogeological studies of water occurrences. The region of Lake Baikal is one of the most studied geodynamically active regions of Russia; therefore, published data from previous studies of the Baikal region were used to interpret the data obtained by the authors.By interpreting the obtained data from the unified tectonophysical positions, the three objectives were met, and the following research results were stated:1. The principal specific features of the geological structure of the crust along the Shertoy-Krasny Chikoy transect are specified. It is established that the divisibility pattern complies with tectonophysical definitions of the hierarchically organized zone-block structure of the lithosphere (Fig. 2, 6, 11, 14, and 16). It is clearly evidenced, within the depth interval from the near-surface to about 30 km, that the crust is split into slightly broken blocks that are in contact with each other via wide zones that are marked by higher fracturing and fluid saturation. To a first approximation, such blocks are shaped as subhorizontal plates in the stable southern regions of East Siberia (e.g., the southern part of the Siberian platform) and subvertical plates in the areas being active in the Cenozoic (e.g., the Baikal rift). Within the framework of the given model of the zone-block structure of the southern regions of East Siberia, strict hierarchical subordination is established that manifests in spatial relationships of interblock zones (the closed network of the zones, imbedded blocks); its quantitative characteristics are stated at the global, trans-regional and three regional levels (Table 1, Fig. 2, Fig. 22). Average sizes of the zones, that were crossed by the transect, are estimated from the depth of their penetration into the crust; it is shown that Scale Invariant 2.2 (previously set for estimates of square areas) is valid also for the analysis of volumes of interblock structures. Detailed observations show that interblock structures are usually wider towards the earth surface; in the 1st order active zones, dimensions of the interblock structures may exceed dimensions of the adjacent, slightly disturbed blocks of the corresponding hierarchic level (Fig. 6, 11, 14, and 16). This pattern is typical of the actively developing Baikal rift and determines specific features of its structure with regards to the zone-block divisibility of the lithosphere.2. The Baikal interblock zone is a global one in the hierarchy of the zone-block structure of Asia. It develops under tension conditions at the contact of the Siberian and Trans-Baikal lithospheric blocks (Fig. 16). Within the transect, the width of the Baikal interblock zone is about 200 km. At the trans-regional level of the hierarchy, the zone is comprised of the Obruchevsky, Chersky-Barguzin and Dzhida-Vitim fault systems (Fig. 6, 11, and 14). The first two of them act as the western and eastern borders of the subsided block of the Baikal basin and thus constitute the major area of the lithospheric extension. The second area is the Dzhida-Vitim fault system separating from the first one by the uplifted Khamar-Daban block; within the transect, it is morphologically manifested by the Ivolgino-Uda basin (Fig. 11, and 16). In this area, due to localization of deformation in the South Baikal basin, the process of fracturing is less pronounced, although indicators of the recent activity, such as seismicity, heat flow, gas emanations etc., are clearly at maximums over the Dzhida-Vitim zone, which makes it evident that this zone is distinguished from the adjacent Transbaikalian block (Fig. 15). Each of the three trans-regional fault systems has a width of about 50 km and consists of regional interblock zones that undergo the intensive development within the Baikal area wherein the crust is subject to extension (Fig. 6, 11, and 14). By their internal patterns, they represent zones of major faults: the Prikhrebtovy, Primorsky, and Morskoy faults constituting the Obruchevsky fault system, as well as the Bortovoy and Deltovy faults from the Chersky-Barguzin system. The Prikhrebtovy and Bortovoy fault zones are located at the periphery of the systems and flatten out in the direction of the rift axis from depths of about 20 km, and, consequently, the area of the most intensive deformations in the Pribaikalie has a ‘bowl-shaped’ profile (Fig. 16). Due to the intensive fracturing occurring in the conditions of the overall stretching of the crust, this area is saturated with meteoric water and deep fluids penetrating into the regional fault zones and partially into the adjacent blocks also belonging to the internal pattern of the Obruchevsky and Chersky-Barguzin fault systems. The block represented by the Baikal basin (located between these two fault systems) is no exception as its central part is disturbed by the regional-scale zone wherein fluidization is most intense due to localization of deformation (Fig. 8, and 16). The zone of the anomalously low resistivity has a width of about 7-10 km and shows no trend to any drastic narrowing in the lower crust, which gives grounds to consider it as the main channel for migration of deep fluids towards the surface.3. As shown by experiences gained during the research at the Shertoy-Krasny Chikoy transect, in East Siberia the applied methods and techniques are informative for identification and analyses of the internal patterns of the interblock zones of different ranks. The methods and techniques used in studies along the transect complement each other and make it possible to investigate different properties of interblock zones. In general, in comparison with blocks, the zones are distinguished by the relief lowering, anomalous water exchange conditions, gas anomalies that are positive and complex in shape, and low resistivity values both near the surface and at depth (Fig. 3–6, 8, and 11–16). Integrated interpretation of the data is challenging: when applied separately, the methods and techniques reveal various specific features of interblock zone that differ in the degree of heterogeneity of the internal patterns depending on conditions of their formation and development. At the current stage of research, the boundaries of the interblock zones can be determined, to a first approximation, from average positions of anomalies, to determine which the deviations of measured parameters from their mean values are used.In the future, it is necessary to conduct detailed surveys using the above geological and geophysical methods in order to reveal specific features of manifestation of the interblock zones that differ in (1) kinematic types, ranks and degrees of activity, (2) properties of infill material and the surrounding medium, and (3) impacts of external factors (e.g., those of the planetary level). Upon comparison of results of such studies, it will be possible to update and improve the proposed generalized models accounting for manifestation of the interblock zones in the geological and geophysical fields (Fig. 17, 20, and 21) and to ensure that the methods and techniques used can be applied more effectively for identification of interblock zones in regions where rock outcrops are poor or lacking.